Smart International Economic SanctionsBetween Political Interests And Humanitarian Considerations (Damascus University Journal for legal sciences, 2026)
economic blockade, which are based on subjecting the people of the target country to harsh living conditions, in order to force it to make a specific change in their policies.However, the damage caused by these sanctions on human rights, prompted the international community to focus on sanctions that are limited to targeting specific people, who are able to influence state policy. These sanctions are known as smart sanctions or targeted sanctions.These smart international economic sanctions were not spared from criticism, whether those related to the scope of their impact, the extent of their effectiveness, and deviation from their goal, or those related to the violation of a number of human rights.
Keywords: Smart sanctions; Human rights